Credit risk management and profitability: empirical evidence on Ethiopian commercial banks - Shibiru Tade Kidane (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2020)
The aim of the study was to assess the impact of credit risk management on the profitability commercial banks in Ethiopia. Secondary data was gathered from National Bank of Ethiopia for ten year periods (2010-2019). The study adopted Correlation analysis and fixed effect Model. Return on Asset was used to measure profitability of commercial banks, bank specific factors(Capital adequacy, Loan and Advances to total deposit, Non- Performing Loans, Bank size and Liquidity and macroeconomic factors (Inflation and Gross Domestic Product) as indicators of credit risk management. The findings showed that Credit Risk Management in terms of bank specific and macroeconomic factors has significant impact on profitability of commercial banks in Ethiopia. Also the result displayed that profitability of commercial banks is not affected by the amount of non- performing loans during the study. The study recommended that banks’ credit risk management should not give due devotion only to the internal factors  but also to external factors exclusively (Gross Domestic Product and Inflation) in order to minimize their negative impact on profitability of commercial banks in Ethiopia